Assessment of the Assistive Technology as Leverage of Revitalizing Libraries Southwestern Nigeria Federal Universities - Alarape, Asimi Akibu; Omoba, Florence Adeola; P., Oghenegweke; G. D., Pelemo (Universitas Pendidikan Indonesia, 2021)
The study investigated the extent of availability of Library Assistive Technology and its influence on library services quality as well as factors that impede its availability and application in Southwestern Nigeria Federal University Libraries. The study adopted descriptive survey research design while population comprised of all library users in the six federal university libraries in Southwestern Nigeria. 1,200 library users were selected using multistage sampling procedure. Questionnaire titled “Library Assistive Technology (LAT) and Service Quality” (LATSQ) was used to gather data analysed using mean, standard deviation and regression analysis. The decision rule was = 2.0 as high extent and 2.0 as low extent, the results showed that LATs were to a high extent available. The findings showed that the overall quality of service exhibited was very high. So also inadequacy power supply, internet facility, ICT infrastructure, settings of the furniture, staff knowledge of the operationalization of LAT, level of LAT skills, high cost of possessing LAT, cost of maintenance of LAT infrastructure, occasional breakdown of LAT facilities, and inadequate funds, The study concluded that the high quality of service delivered is not as a result of availability and usage of various types of library assistive technology.